Psychometric Testing and Semantic Validation of ISPCAN Child Abuse Screening Tool (ICAST) in Urdu Language - Rabia Iftikhar, Farah Malik, (PJE, 2023)
ISPCAN Child abuse screening tool (ICAST) has been used broadly for measuring maltreatment against children. The present study aimed to translate and validate the Child Abuse Screening Tool for two main purposes. Firstly, this scale was translated to use it as a screening tool for the abused children. Secondly, to determine concurrent validity of indigenous Child Abuse Scale (Malik & Shah, 2007) Revision by Malik and Saeed (2014). T